2011
DOI: 10.1542/peds.2010-0809
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Addressing Barriers to Publishing Pediatric Quality Improvement Research

Abstract: Specific, feasible approaches can be used to improve opportunities for publication in pediatric, QI, and general medical journals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Even when CQI projects are disappointing, publishing well-documented experience disseminates valuable experience, an essential goal encouraged by EBM experts. 8, 9, 10, 11 …”
Section: Discussionmentioning
confidence: 99%
“…Even when CQI projects are disappointing, publishing well-documented experience disseminates valuable experience, an essential goal encouraged by EBM experts. 8, 9, 10, 11 …”
Section: Discussionmentioning
confidence: 99%
“…13 Conducting and publishing QI efforts is an important task to promote transparency and disseminate knowledge as to why interventions succeed or fail, and if rigorous pre-and postintervention data collection are analyzed, then bias and confounders are reduced. 14 Emphasize noninvasive respiratory support using NCPAP. Continue fluid restriction advancing gradually up to 120-130 mL/kg/day total fluids while the PDA is present.…”
Section: Discussionmentioning
confidence: 99%
“…Few QI projects reach publication, however, partly because the design, types of intervention, data collection and analysis related to QI do not fit traditional publication guidelines. Van Cleave et al 16 identified other barriers to publishing, including small-scale local initiatives, and strategies to overcome these, including working in networks and creating incentives.…”
Section: Sharing Learningmentioning
confidence: 99%